Pengaruh Brand Image, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Yamaha N-Max Di Kota Rantauprapat - Nelpy D Simbolon; Yuniman Zebua; Abdul Halim (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This research aims to determine the influence of brand image, product quality and price on purchasing decisions for Yamaha Nmax in Rantauprapat City. The sample in this research was 97 consumers who had purchased Yamaha Nmax products. The method used in this research is a quantitative descriptive method. The research results state that brand image, product quality and price have a positive and significant effect on purchasing decisions both partially and simultaneously. Judging from the coefficient of determination, it is 38.8%, which means that purchasing decisions are influenced by the variables brand image, product quality and price, and the remaining 62.2% is influenced by other variables not examined in this research.